1975
DOI: 10.1021/jm00243a012
|View full text |Cite
|
Sign up to set email alerts
|

Potential bioreductive alkylating agents. 5. Antineoplastic activity of quinoline-5,8-diones, naphthazarins, and naphthoquinones

Abstract: A number of 2-chloromethyl and 2-bromomethyl derivatives of naphthoquinones, quinolinediones, and naphthazarins were designed and synthesized as potential bioreductive alkylating agents, and the antitumor activity of these compounds was assessed in mice bearing Sarcoma 180 ascites cells. The results indicated that, with the exception of 3-benzamido-2-chloromethyl-1,4-naphthoquinone, which was inactive, all newly synthesized naphthoquinones possessed strong antitumor activity against this neoplasm. 6,7-Bis(brom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 4 publications
0
35
0
Order By: Relevance
“…For example, benzoquinones of structural type (I) are less active than the analogous naphthoquinones. The range of half-wave potentials for the former was found to be between -0.03 and -0.11 V, and for the latter the range was from -0.23 to -0.31 V. Recently, a series of 2-substituted-9,10-anthraquinones ( 5 ) having half-wave reduction potentials of from -0.52 to -0.56 V were found to show greater toxicity to chronically hypoxic EMT6 tumor cells than for those grown in the presence of oxygen.' Quinone methide formation can again be viewed as arising from the anthraquinones a s represented below.…”
Section: A Quinone Methides Via Bioreduction-modelmentioning
confidence: 99%
“…For example, benzoquinones of structural type (I) are less active than the analogous naphthoquinones. The range of half-wave potentials for the former was found to be between -0.03 and -0.11 V, and for the latter the range was from -0.23 to -0.31 V. Recently, a series of 2-substituted-9,10-anthraquinones ( 5 ) having half-wave reduction potentials of from -0.52 to -0.56 V were found to show greater toxicity to chronically hypoxic EMT6 tumor cells than for those grown in the presence of oxygen.' Quinone methide formation can again be viewed as arising from the anthraquinones a s represented below.…”
Section: A Quinone Methides Via Bioreduction-modelmentioning
confidence: 99%
“…3 Their role as electron transfer agents in primary metabolic processes like photosynthesis and respiration is vital to human life. A large number of chemical derivatives with 1,4-benzoquinone as the basic subunit exhibit prominent pharmacological applications such as antibiotic, 4,5 antitumor, [6][7][8][9] antimalarial, 7,10 antineoplastic, 11 anticoagulant 12 and herbicidal activity. 13 Wide applications of quinones can also be found in the field of synthetic organic chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Those compounds that possessed the most negative half-wave reduction potential, i.e., those compounds that were difficult to reduce, demonstrated the highest activity against sarcoma 180 tumor growth. Lin et al (7,8) suggested that those quinone deriva- Greater than 80% inhibition is required for significant activity. * n = 6. c T/C % > 125 is required for significant activity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, dichloroallylawsone is currently in clinical trials in the United States (1)(2)(3)(4)(5)(6)(7)(8). An investigation of sulfone analogs of naphthoquinones was undertaken recently (9), resulting in a series of substituted thiochromones and thiochroman-4-ones and their 1,l-dioxides.…”
mentioning
confidence: 99%